Research and assessment of wind turbine's noise in Vydmantai - Jaskelevičius, Bronius; Užpelkienė, Natalija (Journal of Environmental Engineering and Landscape Management, 2008)
The decreasing reserve and growing costs of coal, oil and gas has persistently led us to use renewable energy resources. Using them environmental harm, air pollution and greenhouse effect can significantly be decreased. According to the European Union Parliament's and Council Directive 2001/77/EC approved in July 27, 2001, the member countries (Lithuania has been a member country from May 1, 2004) must seek to use not less than 12 per cent of renewable energy sources in total energy balance and 22,1 percent in the country's energy balance (including large hydroelectric power station). The numbers are significant. Thus, using wind energy can be one of the ways to fulfil the requirements. Lithuanian seaside, where the strongest winds are blowing, has been the most favourable place for the wind turbine's installation. However, usage and development of wind energy has been facing resistance from the society. One of the biggest arguments against the wind turbine is the noise which can cause inconveniences for the permanent residents and holidaymakers of the health‐resort zone. Therefore, environmental impact of the wind turbine requires exhaustive investigations. The research was carried out in the vicinity around the only one presently active industrial wind turbine in Vydmantai (region of Klaipeda, Lithuania). During the investigation it was established that the highest noise level was registered opposite the airscrew. The smallest noise level was measured in both sides from the tower in windscrew plane. It has been measured that noise level is noticeably higher in Vydmantai wind turbine's zone than in the background, which does exceed 250–300 m (5–6 windscrew diameters).Vydmantų vėjo jėgainės keliamo triukšmo tyrimai ir įvertinimasSantrauka. Mažėjančios akmens anglies, naftos ir dujų atsargos elektros gamyboje verčia naudoti kitus energijos šaltinius, tokius kaip atsinaujinantieji energijos šaltiniai, kurie gali sumažinti aplinkos žalojimą, atmosferos teršimą, šiltnamio efektą. Remiantis Europos Sąjungos Parlamento ir Tarybos 2001 07 27 direktyva 2001/77/EB šalys narės (nuo 2004 05 01 ir Lietuva) turi siekti, kad 2010 m. atsinaujinančiųjų energijos išteklių dalis bendrame energijos balanse sudarytų ne mažiau kaip 12 %, o šalies elektros balanse 22,1 % (su didelėmis hidroelektrinėmis). Tai dideli skaičiai. Šis padidėjimas galimas visų pirma pasitelkus vėjo energetiką. Šiuo metu pastebėta, kad vėjo energetika susilaukia  visuomenės pasipriešinimo. Vienas iš pa-grindinių motyvų – šių jėgainių keliamas triukšmas. Atsižvelgiant į tai, kad vėjo jėgainių statybai Lietuvos pajūris yra palankiausia vieta, kur yra daug smulkių gyvenviečių ir poilsiaviečių zonų, šiam vėjo jėgainių poveikiui ištirti reikėjo papildomų išsamių tyrimų. Šie tyrimai buvo atlikti Vydmantuose (Klaipėdos rajonas) prie veikiančios pramoninės vėjo jėgainės. Tyrimais nustatyta, kad didžiausias triukšmo lygis buvo registruotas priešais vėjaratį. Mažiausias triukšmo lygis buvo išmatuotas į abi puses nuo bokšto vėjaračio plokštumoje. Vydmantų vėjo jėgainės zona, kurioje triukšmų lygis yra didesnis nei foninis, neviršija 250–300 m (5–6 vėjaračio skersmenys).Reikšminiai žodžiai: vėjo energetika, vėjo jėgainė, vėjo jėgainių keliamas triukšmas, vėjaračio orientacija, triukšmo  lygis.Исследование и оценка шума видмантайской ветряной энергоустановкиРезюме. Уменьшающиеся запасы каменного угля, нефти и газа способствуют применению альтернативных источников энергии для её получения, например, возобновляемых источников энергии, которые могут уменьшить наносимый окружающей среде вред, а также снизить уровень загрязнения атмосферы и тепличный эффект. Руководствуясь директивой Европейского Союза 2001/77/ЕС, страны, входящие в его состав (с 01-05-2004 и Литва), должны стремиться к тому, чтобы к 2010 г. часть электроэнергии, получаемой из возобновляемых источников энергии, составляла не менее 12 % в общем энергетическом балансе и 22,1 % (включая крупные гидроэлектростанции) в энергетическом балансе страны. Это большие цифры. Их достижение возможно прежде всего благодаря использованию энергии ветра. Однако в настоящее время ветроэнергетика вызвала недовольство общественности. Одним из основных мотивов недовольства является шум, распространяемый ветряными электростанциями. В Литве наиболее приемлемым местом для строительства ветрогенераторов является приморье, где находится много мелких населённых пунктов, а также зон туризма и отдыха, поэтому фактор общественного недовольства требует серьёзных всесторонних исследований. С этой целью исследовался шум, распространяемый ветряной электроустановкой, находящейся в городе Видмантай (Кретингский р-он). Результаты исследования показали, что наибольший уровень шума наблюдался перед ветровиком, а наименьший – по обе стороны от башни установки в плоскости ветровика. Зона, в которой уровень шума выше фонового, не превышает 250–300 м (5–6 диаметров ветровика).Ключевые слова: энергетика ветра, ветряная энергоустановка, ориентация ветровика, уровень шума.First Published Online: 14 Oct 2010